Mesenteric Panniculitis (MP): A Frequent Coincidental CT Finding of Debatable Clinical Significance - Gögebakan, Özlem; Osterhoff, Martin A.; Albrecht, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Background Mesenteric panniculitis (MP) is histologically characterized by chronic nonspecific inflammation of the adipose tissue of the intestinal mesentery with unclear etiology. MP occurs predominantly in men, mostly in mid to late adulthood. MP is typically found as an incidental diagnosis on abdominal CT.Methods A comprehensive review of the literature including case reports and cohort studies was performed. Therefore, a global search in PubMed was carried out. Search terms were (and/or) “mesenteric panniculitis”, “panniculitis mesenterialis”, “mesenteric lymph nodes”, “CT”, “imaging”, “sclerosing mesenteritis”, “case report”, “therapy”.Results and Conclusion MP is a relatively common CT finding. The true prevalence seems to be higher than the reported 0.6 % to 2.4 % due to underreporting. The most important differential diagnosis is malignant lymphoma, which may be difficult to distinguish from MP. The majority of patients with MP are clinically asymptomatic and do not require therapy. In rare symptomatic cases, non-specific symptoms like abdominal pain, fever, nausea or vomiting occur. For therapy, glucocorticoids and tamoxifen have been suggested. Several studies suggested that MP is associated with other diseases and might be a paraneoplastic phenomenon, but four recently published case-control studies suggest that MP is an independent non-specific benign age-related phenomenon. However, two further studies show a possible association of MP with malignant lymphoma. The clinical relevance of MP remains the subject of scientific debate.Key Points: Citation Format
Keywords: abdomen; CT; mesentery; inflammation; lymphoma; paraneoplastic phenomenon